Biorefineries and chemical processes : design, integration and sustainability analysis - Sadhukhan, Jhuma; Ng, Kok Siew; Hernandez, Elias Martinez (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2014)
"This book is for educators, postgraduate and final year undergraduate students in chemical engineering, environmental and biochemical engineering and applied science subjects, as well as researchers and practitioners in industry"--
4.6 LCA: Impact Assessment4.6.1 Global Warming Potential; 4.6.2 Land Use; 4.6.3 Resource Use; 4.6.4 Ozone Layer Depletion; 4.6.5 Acidification Potential; 4.6.6 Photochemical Oxidant Creation Potential; 4.6.7 Aquatic Ecotoxicity; 4.6.8 Eutrophication Potential; 4.6.9 Biodiversity; 4.7 LCA: Interpretation; 4.7.1 Stand-Alone LCA; 4.7.2 Accounting LCA; 4.7.3 Change Oriented LCA; 4.7.4 Allocation Method; 4.8 LCIA Methods; 4.9 Future R & D Needs; References; 5 Data Uncertainty and Multicriteria Analyses; 5.1 Data Uncertainty Analysis; 5.1.1 Dominance Analysis; 5.1.2 Contribution Analysis.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biomass -- Refining; Biomass chemicals -- Technological innovations; Biomass chemicals industry; Biomass energy industries -- Environmental aspects; Biomass -- Refining; Biomass chemicals -- Technological innovations; Biomass chemicals industry; Biomass energy industries -- Environmental aspects; Biomasse -- Affinage; Produits chimiques de la biomasse -- Innovations; Biomasse -- Industrie; Biomasse -- Industrie -- Aspect de l'environnement.; SCIENCE -- Chemistry -- General; Electronic books